Long-read sequencing identifies the pathogenic nucleotide repeat expansion in RFC1 in a Japanese case of CANVAS - Nakamura, Haruko; Doi, Hiroshi; Mitsuhashi, Satomi; Miyatake, Satoko; Katoh, Kazutaka; Frith, Martin C.; Asano, Tetsuya; Kudo, Yosuke; Ikeda, Takuya; Kubota, Shun; Kunii, Misako; Kitazawa, Yu; et al. (Journal of human genetics, 2020)
Recently, a recessively inherited intronic repeat expansion in replication factor C1 (RFC1) was identified in cerebellar ataxia with neuropathy and bilateral vestibular areflexia syndrome (CANVAS). Here, we describe a Japanese case of genetically confirmed CANVAS with autonomic failure and auditory hallucination. The case showed impaired uptake of iodine-123-metaiodobenzylguanidine and I-ioflupane in the cardiac sympathetic nerve and dopaminergic neurons, respectively, by single-photon emission computed tomography. Long-read sequencing identified biallelic pathogenic (AAGGG)n nucleotide repeat expansion in RFC1 and heterozygous benign (TAAAA)n and (TAGAA)n expansions in brain expressed, associated with NEDD4 (BEAN1). Enrichment of the repeat regions in RFC1 and BEAN1 using a Cas9-mediated system clearly distinguished between pathogenic and benign repeat expansions. The haplotype around RFC1 indicated that the (AAGGG)n expansion in our case was on the same ancestral allele as that of European cases. Thus, long-read sequencing facilitates precise genetic diagnosis of diseases with complex repeat structures and various expansions.